Identification and evaluation of (3Z,6Z,8E)-dodeca-3,6,8-trien-1-ol as the trail following pheromone on Microcerotermes exiguus (Isoptera:Termitidae) - Lubes, Giuseppe (2018)
Trail-following pheromone is one of the most important semiochemical in termites. This pheromone is responsible for the recruitment of individuals from the colony to perform different tasks. The aim of this work was to isolate and identify the trail-following pheromone of Microcerotermes exiguus (Isoptera: Termitidae), a typical termite from the Neotropic, that is considered pest in some crops. Subterranean nest of M. exiguus were collected with a shovel in Caracas, Venezuela in 2010. Different chemical micro-reactions combined with chromatographic analysis of solvent extracts, as well as solid phase microextraction analyses (SPME) were applied to termite sternal glands; besides, some behavioral biossays were undertaken. A peak in the chromatograms from extracts (retention index: 1483), presented a fragmentation pattern with m/z ions: 41; 55; 67; 79; 91; 105; 119; 135; 142; 180, this result alongside behavioral assays allowed us to conclude that (3Z,6Z,8E)-dodeca-3,6,8-trien-1-ol (DTOH) acts as the main component of the trail following pheromone. The estimated optimum concentration for termite recruitment and orientation was around 1 pg/cm, being statistically comparable to the value on trails marked with whole body extracts at concentration of 1 worker/cm. The period of time that this compound takes to recruit other colony members is 13.67 ± 5.76 s and lasts up to two hours. Both analytical and behavioral results provided better understanding on the chemical communication of M. exiguus. This information could be used for the future development of newer pest control methods.